Risks associated to different methods of increasing pregnancy rate of cows in cow-calf systems - Oliveira, Tamara Esteves de (2018)
This study assessed the risks of different management practices to increase pregnancy rate in beef cow-calf systems, aiming at assisting decision-making. The perception of 18 experts on animal sciences regarding the risks of 32 nutritional, breeding, and general management practices applied to increase pregnancy rate were evaluated through questionnaires. The experts were selected by a non-probability sampling of researchers on veterinary and animal sciences. In addition, five farmers and eight technical consultants were also selected. The questionnaire was applied during a face-to-face meeting. The risk of each practice was assessed according to four factors, namely, cost, technical knowledge, operational complexity, and flexibility, and an equation was developed to calculate this risk. The applied method allowed to determine the risk of each practice, obtaining results similar to those previously perceived by the experts. Operational complexity and cost had greater influence on the estimated risks compared with the other factors. Moreover, the increase of one unit in operational complexity and cost increased the perceived risk and the estimated risk scores in 0.43 and 0.28 points, respectively. Overall, the application of general management practices presented lower risk score compared with nutritional and breeding practices, which were not different from which other. Equations to estimate the risks of farm managers should routinely apply management practices to increase the efficiency of cow-calf production systems.